Manganese-catalyzed direct conversion of ester to amide with liberation of H 2 - Mondal, Akash; Subaramanian, Murugan; Avanashiappan, Nandakumar; Balaraman, Kambaram (Organic Letters, 2018)
A simple and efficient Mn-catalyzed acylation of amines is achieved using both acyl and alkoxy functions of unactivated esters with the liberation of molecular hydrogen as a sole byproduct. The present protocol provides an atom-economical and sustainable route for the synthesis of amides from esters by employing an earth-abundant manganese salt and inexpensive phosphine-free tridentate ligand.